Action research: enriching the teaching repertoire in class / Sallehuddin Ismail, Nurliza Muslim and Nik Ismail Harun - Ismail, Sallehuddin; Muslim, Nurliza; Harun, Nik Ismail (2003)
Educational research has been successfully assisting educators in solving enormous problems and difficulties in education especially in the teaching and learning activities in the classroom. Educators may benefit by taking a close and critical insight in their own practices. Developed and refined insights as to the nature of that practice, professional autonomy and competence, and authority to give a reasoned justification for their own educational practice may fruitfully result. The concept 'educational' involves the notion of 'improvement'. By being aware and critical of their practice, educators work more positively towards their own professional development. Improvements in the quality of education are dependent upon the professional competence and high morale of the educators. This paper tries to promote action research in improving teaching and learning activities in the classroom. Through its emphasis on critical evaluation of practice within a democratic framework, the action research movement has integrated researchers from different disciplines and curriculum areas who share a concern to improve practice and to understand the process of improving practice. The paper gives the background and explanations for action research and the implications for educators who embark on an action research project, the pitfalls as well as the satisfaction. The paper intends to be an organic instrument in bringing people together to adopt in-service strategies that deliberately and systematically set out to encourage educators to raise the level of their awareness, being open to new concepts and developing professional competence. Action research presents an opportunity for educators to become uniquely involved in their own practice, to professionalize themselves, and to give reasoned justification for what they are doing.